A Novel Ourmia-Like Mycovirus Confers Hypovirulence-Associated Traits on Fusarium oxysporum - Zhao, Ying; Zhang, Yuanyan; Wan, Xinru; She, Yuanyuan; Li, Min; Xi, Huijun; Xie, Jiatao; Wen, Caiyi (Frontiers in Microbiology, 2020)
Fusarium wilt caused by Fusarium oxysporum f. sp. momordicae (FoM) is an important fungal disease that affects the production of bitter gourd. Hypovirulence-associated mycoviruses have great potential and application prospects for controlling the fungal disease. In this study, a novel ourmia-like virus, named Fusarium oxysporum ourmia-like virus 1 (FoOuLV1), was isolated from FoM strain HuN8. The viral genomic RNA is 2,712 nucleotides (nt) in length and contains an open reading frame (ORF) encoding a putative RNA-dependent RNA polymerase (RdRp) using either standard or mitochondrial codes. In strain HuN8, there was also a FoOuLV1-associated RNA segment with 1,173 nt in length with no sequence homology. Phylogenetic analysis showed that FoOuLV1 is a member of the genus Magoulivirus of the family Botourmiaviridae. FoOuLV1 was found to be associated with hypovirulence in FoM. Moreover, FoOuLV1 and its hypovirulence trait can be transmitted horizontally to other FoM strains and also to other formae speciale strains of F. oxysporum. In addition, FoOuLV1 showed significant biological control effect against the bitter gourd Fusarium wilt. To our knowledge, this study reveals the first description of a hypovirulence-associated ourmia-like mycovirus, which has the potential to the biological control of Fusarium wilt.